Bilateral transmigration of impacted mandibular canines: report of two cases and review - Qaradaghi, Idris Faiq (Archives of Oral Research, 2010)
Objective: To present and discuss a rare case of transmigration of bilateral mandibular canines. To review the literature and to discuss treatment. Discussion: Transmigration of the canine tooth is an uncommonphenomenon, often undetected in routine dental examinations. The less common finding is type 5 (the canine is positioned vertically in the midline with the long axis of the tooth crossing the midline)and the least common phenomenon is bilateral occurrence of type 5. There is no known etiology for its occurrence. Conclusion: Transmigration of mandibular canines across the midline is a rare condition. An even less common finding is bilateral transmigration of canines across the midline.